The Reality of Investigative Journalism in the Faculties of Mass Communication in Jordanian Universities. - jwaniat, marcelle (Arts and Social Sciences Series, 2026)
Objectives: The aim of the study was to identify the reality of investigative journalism in the faculties of media in Jordanian universities, the extent of the students’ interest in investigative journalism among the students of the Department of Journalism and Digital Media in Jordanian universities, the cognitive, emotional and behavioral attitudes of students towards investigative journalism, and the academic reasons that affect the inclusion of in-depth investigative journalism courses in the study plans from the point of view of media professors. Methodology: This study falls under the category of descriptive research and relied on the quantitative approach. The study population consisted of two categories: the first being media students (526 individuals) and the second being media professors (52 individuals) in the following Jordanian universities: (Yarmouk University, Zarqa University, Middle East University, Jadara University, Arab Open University, Petra University, Applied Science University, Aqaba University of Technology). Two separate questionnaires were used for both categories to suit the nature of the target sample. Results: It was found that the interest of the students of the departments of journalism and digital media in Jordanian universities in investigative journalism came to a high degree, with an arithmetic average of 2.62, and that the negative cognitive, emotional and behavioral attitudes of the students of the Department of Journalism and Digital Media in Jordanian universities towards Jordanian investigative journalism came to a high degree, respectively, with a total arithmetic average for each direction (2.46 / 2.51 / 2.50) and that the most important academic reasons affecting the inclusion of investigative journalism courses in The study plans of the faculties of mass communication in Jordanian universities are represented by the existence of obstacles related to the freedom of investigative journalism from the point of view of media professors. Conclusion: The need to promote investigative journalism courses in media study plans in Jordanian universities, and the need to qualify and train students of media faculties in Jordanian universities through holding specialized workshops and training courses in investigative journalism. Keywords: Investigative Journalism, Media Faculties, Jordanian Universities